Job stability, mobility and labour market restructuring: Evidence from German microdata - Marcel Erlinghagen (Management Revue, 2006)
The paper analyses the change of job stability and its determinants in the course of time by presenting some empirical evidence from Germany. Drawing upon event history data from the German Federal Labour Office insurance accounts and employing Cox Proportional Hazard Rate Models, we test six core hypotheses on labour market restructuring and its impacts on job stability. Our analysis suggests that during the transition to service society between the 1980s and the 1990s some kind of 'restructuring' of the German labour market has taken place that has simultaneously led to an increasing polarisation and to an increasing levelling out of individual employment chances and risks.
Keywords: 650; job stability; flexibility; Germany; event history analyses; Arbeitsplatzsicherung; Arbeitsmobilität; Arbeitsmarktflexibilität; Schätzung; Deutschland